Estimation of the uncertainty in the barium analytical technique in wastewater by atomic absorption spectrometry - Camero Jiménez, José W. (2013)
This paper aims to estimate the measurement uncertainty of the method Standard Methods 3111 D - Direct Nitrous Oxide - Acetylene Flame Method for the determination of barium in the wastewater matrix by atomic absorption spectrometry, using a model estimation uncertainty factors as requested by the guideline INDECOPI-acr-09 CRT-D, low approach quality management system of testing laboratories ISO / IEC 17025:2005.